Modelling of Silt-detention As Small In-channel Silt-detention Reservoirs - Ghodichor, R.S.; Satyanarayan, T.; Misra, K. (Journal of Soil and Water Conservation, 2022)
The silt-detention in some selected silt-detention reservoirs, con- structed by the Engineering Division, Soil Conservation Department, DVC, Hazaribagh, in the subcatchment 7 of the DM", were studied. The sedimentation survey records „of periodic surveys conducted over these reservoirs were analysed. The results show that there exists a non-linear relationship between the capacity loss rate and the capacity-inflow ratio. It is also observed that capacity loss rate and the capacity-inflow ratio decreases with the age of reservoir. A method is suggested to estimate the volume of sediment detained and the life of unaccessed silt-detention reservoirs in steps by. selecting specified time intervals representing the time of opportunity of sedimentation. The model and the curve can also be used where Bruna's Trap Efficiency Curve can not be used as the latter 's use is recommended for water storage reservoirs.